Effects of irradiated biodegradable polymer in endothelial cell monolayer formation - Arbeitman, Claudia Roxana (2013)
In this work we study cell adhesion, proliferation and cell morphology of endothelial cell cultured on poly-l-lactide acid (PLLA) modified by heavy ion irradiation. Thin films of PLLA samples were irradiated with sulfur (S) at energies of 75 MeV and gold (Au) at 18 MeV ion-beams. Ion beams were provided by the Tandar (Buenos Aires, Argentina) and Tandetron (Porto Alegre, Brazil) accelerators, respectively. The growth of a monolayer of bovine aortic endothelial cells (BAEC) onto unirradiated and irradiated surfaces has been studied by in vitro techniques in static culture. Cell viability and proliferation increased on modified substrates. But the results on unirradiated samples, indicate cell death (necrosis/apoptosis) with the consequent decrease in proliferation. We analyzed the correlation between irradiation parameters and cell metabolism and morphology.